Quality Characteristics of Wheat Malts with Different Country of Origin and Their Effect on Beer Brewing - Yang Soo Byeon; Seung-Taik Lim; Hyun-Jin Kim; Han Sub Kwak; Sang Sook Kim (Journal of Food Quality)
The characteristics of wheat malt, wort, and beer from two Korean wheat varieties (Keumkang and Anzunbaengi; KM and AM, respectively) were compared to those of two commercial wheat malt controls from the USA and Germany (UM and GM), to examine the feasibility of Korean wheat for brewing. The quality parameters of four wheat malts, chemical properties of wort using them, volatile compounds, sensory attributes, and consumer acceptability of four final beers (KB, AB, UB, and GB) were analysed. Additionally, the relationship of each parameter was determined through multiple factor analysis. Korean wheat malts were different from control malts in free amino nitrogen (FAN), soluble and total nitrogen, and Kolbach index. The extract (81.8–83.2%) and diastatic power (407–477 WK°) of all samples were in the brewing field’s recommended range. The FAN and yeast cell population of the wort samples were similar during fermentation except on the initial day, which showed a high FAN and yeast cell population for KM wort. Eleven volatile compounds with variable importance in projection scores above 1.0 were responsible for discrimination of the beer samples by partial least squares discriminant analysis. The four beer samples’ overall acceptance scores were not significantly different. However, their acceptance trends were different depending on consumer preference segments by agglomerative hierarchical clustering analysis, implying the need for product development depending on the target consumer. Regarding sensory attributes, KB had a less fruity flavour than the other beer samples (p<0.05) and sweetness of AB tended to be higher than the others. An association plot based on multiple factor analysis of the wheat beer samples, volatile compounds, sensory properties, and overall acceptance showed that sweetness, alcohol aroma, and fruity flavour were closely associated with AB and overall acceptance, while 2,3-butanediol and turbidity were placed opposite side of there.